Construction and Application of an Economic Intelligent Decision-making Platform Based on Artificial Intelligence Technology - Chen, Jing (Informatica, 2024)
With the rapid development of artificial intelligence technology, which has promoted the rise of information technology and e-government, various government departments have accumulated a large amount of macroeconomic data. Faced with a large amount of economic data, how to analyse and utilise these data and provide references for decision-making is the main problem currently faced. Online analytical processing (OLAP) is a data warehouse tool for the interactive analysis of multidimensional data in various dimensions. In this paper, OLAP is applied to macroeconomic data analysis and mining, and an economically intelligent decision-making platform is built to analyse economic indicator data from multiple perspectives and in multiple dimensions. The platform implements OLAP modelling, metadata management, OLAP analysis and report query. In the pre-calculation and update algorithm of data cubes in OLAP modelling, a multiplexed cube aggregation complete cube calculation algorithm is proposed, and the contents of the algorithm are analysed in detail. Practical application shows that the algorithm is feasible and easy to implement, and it supports the calculation of large data volume cubes and can use time slicing to update data cubes, effectively ensuring the timeliness and reliability of economic data information.